Effects of Pine Pollen Extract in Relieving Hot Flushes in Sex Hormone-Deficienct Rats - Chamawan, Panida; Thisayakorn, Krittiya; Phornchirasilp, Srichan (Journal of Basic and Applied Pharmacology, 2017)
Hot flushes or hot flashes are one of the vasomotor symptoms frequently found in menopausal women and andropausal men. Pine pollen has been used in traditional Chinese medicine (TCM) for health restoration, anti-aging, and longevity tonic supplements. Since Scotch pine contains steroid hormones, it has been claimed for maintaining men’s health. This study aimed to investigate the effects of pine pollen extract from Pinus patula ssp. tecunumanii in relieving hot flushes in rats with sex hormone depletion. Alpha-calcitonin gene-related peptide (αCGRP) was injected into female rats every other day for tail skin temperature (TST) elevation. Pine pollen extract significantly reduced TST in a concentration-dependent manner on the 3rd day of oral administration. Conjugated equine estrogen (CEE), used for estrogen replacement therapy, spent more time to reduce TST than pine pollen extract did (the 6th day of administration), and continuously decreased TST until the end of experiment. While TST in male rats was increased by daily injection of leuprorelin acetate, the pine pollen extract significantly reduced TST in a dose dependent manner on the 2nd day of oral administration. Testosterone undecanoate (TU), used for hormone replacement therapy in men, significantly reduced TST on every days of oral administration. The ELISA results showed that uterine estrogen concentrations of CEE and pine pollen extract treated groups were significantly higher than control while no significant difference in serum estrogen levels was found. Only serum testosterone concentration of TU treated group was significantly higher than control while testis weights of all groups were lower than sham-treated group. Pine pollen extract from Pinus patula ssp. tecunumanii could be classified as a phyto-androgen that might balance testosterone and estrogen levels, resulting in alleviating the symptoms of sex hormone deficiency such as hot flushes, night sweating, and sleep disturbance.